The wisdom of the intermediary: the role, function, and ways-of-being of the intermediary in a strategic program for university-industry relations - Lars Frølund; Morten Ziethen (Triple Helix, 2016)
This paper is an inquiry into the human factor in intermediation. We argue that we have not yet fully grasped the different roles, functions, and ways-of-being of the intermediary and that the concept of first- and second-order 'wisdom' is helpful in understanding what it takes to succeed as an intermediary. Through a comprehensive inquiry into human intermediaries in a corporate strategic program for university-industry collaboration in a global company, we develop a typology based on three fundamental roles: the 'Power Promoter,' the Diplomat, and the Creative Integrator. On this basis, we argue that the wisdom of the intermediary involves mastering the different roles (first-order wisdom) and deciding between them in each individual situation of intermediation (second-order wisdom). As a result, we advance Hargadon and Sutton's initial insight into the human factor in intermediation, thereby further humanizing the research on intermediation.
Keywords: 330; Intermediaries; Knowledge brokering; Triple helix; University-industry collaboration; Wisdom